Leveraging fluorinated glucosamine action to boost anti-tumor immunity - Dimitroff, Charles J. (2012)
N-acetyllactosaminyl glycans are key regulators of the vitality and effector function of anti-tumor T cells. When galectin-1 (Gal-1) binds N-acetyllactosamines on select membrane glycoproteins on anti-tumor T cells, these cells either undergo apoptosis or become immunoregulatory. Methods designed to antagonize expression or function of these N-acetyllactosamines on N- and O-glycans have thus intensified. Since tumors can produce an abundance of Gal-1, Gal-1 is considered a critical factor for protecting tumor cells from T cell-mediated anti-tumor activity. Recent efforts have capitalized on the anti-N-acetyllactosamine action of fluorinated glucosamines to treat anti-tumor T cells, resulting in diminished Gal-1-binding and higher anti-tumor T cell levels. In this perspective, the prospect of fluorinated glucosamines in eliminating N-acetyllactosamines on anti-tumor T cells to boost anti-tumor immunity is presented.